Gender-Leading Opportunities for Women Tax Policy: A Strategic Tax Policy Framework to Address Gender Wage - Diyono, Annisa Sastro; Vambia, Annisa Desty; Manihuruk, Jessica Benedicta; Kurniawan, Viena; Vito, Yehezkiel (Jurnal Akuntansi Dan Manajemen, 2025)
This paper explores the implementation of gender-responsive tax policies in Indonesia to address persistent economic disparities between men and women, particularly the gender wage gap. Gender inequality, especially in wages, continues to be a significant issue in Indonesia. According to the International Labor Organization (ILO) Global Wage Report 2018/2019, women only earn an average wage of around 20% lower than men worldwide (ILO, 2024). Meanwhile, according to the infographics from UN Women Indonesia (2020), there is a gap of around 16% between men's and women's wages in Indonesia, highlighting how gender inequality generates a significant impact on women in various aspects of life, including health, education, and business life. During Indonesia's G20 Presidency, the concept of Gender-Based Tax (GBT) was introduced as a potential solution. However, detailed implementation strategies for GBT remain underdeveloped. We propose the GLOW (Gender-Leading Opportunities for Women) scheme to address this gap. This framework includes tax reductions for female micro, small, and medium-sized enterprises (MSMEs), incentives for female employees, and VAT exemptions on essential products for women. Additionally, the scheme involves collaboration with Renjani Volunteer, a program under the Directorate General of Taxes. The research compares Indonesia’s approach to GBT with similar policies in other countries to assess their effectiveness and adaptability to local needs. Employing a normative juridical method, the study analyzes relevant legal norms by examining legislation, legal literature, and official documents. This analysis provides real-world insights into the practical application of gender-based taxation. The findings reveal that the GLOW scheme holds significant potential to reduce gender inequality by empowering women economically, particularly through financial independence. By focusing on women-owned MSMEs, incentivizing female participation in the workforce, and ensuring tax relief on essential products, this proposal aligns with the broader goals of Sustainable Development Goal 5 (gender equality). The paper concludes that implementing the GLOW scheme could serve as a progressive step toward achieving gender equity in Indonesia, contributing to both economic growth and social inclusion.